Study of correlation of maternal and perinatal outcome with interpregnancy interval at a tertiary care centre - Mona Asnani; Anjoo Agarwal; Renu Singh; Sunita Singh (Barpeta Obstetrics and Gynaecological Society, 2023)
Background: Interpregnancy interval (IPI) or birth to pregnancy interval is defined as time interval between live birth and beginning of following pregnancy. Interpregnancy interval has been shown to be an important prognostic marker for perinatal outcome. According to WHO atleast 24 months of interpregnancy interval is optimal. Objective: This study was planned to correlate maternal and perinatal outcome with interpregnancy interval at a tertiary care centre in northern India. Materials and methods: The study was a cross sectional observational study. It was conducted in department of obstetrics and gynecology, KGMU Lucknow. All pregnant women beyond period of viability, delivering at our centre, irrespective of live or stillborn were included in the study. Maternal and perinatal outcome of all the patients was observed. Results: 212 women were assessed in terms of interpregnancy interval and its correlation with maternal and perinatal outcome. Of these 212 women interval less than or equal to 24 months, 125 had interpregnancy interval >24 months. Proper antenatal registration (4 visits atleast) was more in IPI more than 24 months group. Severe anemia and non severe preeclampsia was found to be more in group with IPI ≤24 months than group IPI> 24 months. Perinatal outcome was found to be far better in group IPI> 24 months as compared to group with IPI ≤24 months in terms of perinatal mortality, preterm births, low birth weight and admission to neonatal unit / neonatal ICU. Conclusion: Our study concludes that there is a significant impact of interpregnancy interval on maternal and perinatal outcome which also signifies the importance of spacing and contraception. However this study being a small pilot study, further larger studies are required on this topic in future to consolidate the results.